Marvin and the moths - Holm, Matthew; Follett, Jonathan (Scholastic Press, 2016)
Middle school is off to a depressing start for Marvin Watson, his new baby brother is proving to be a disappointment, and now his town is being threatened by a horde of mutant bugs, including a hungry spider that quotes Shakespeare--and if that is not enough there are three sarcastic man-sized moths living in the attic.